2019
DOI: 10.3390/ani9030090
|View full text |Cite
|
Sign up to set email alerts
|

Production Phase Affects the Bioaerosol Microbial Composition and Functional Potential in Swine Confinement Buildings

Abstract: Bioaerosols from swine confinement buildings (SCBs) pose a challenge to public health,and microorganisms within the SCBs bioaerosols originate from swine feces, of which the microbialcomposition is associated with the production phase. The present study adopted the wholemetagenome shotgun sequencing approach, to assess the effects of the production phase on thecomposition and functional potential of microbial populations in SCBs bioaerosols. Most annotatedproteins were assigned into domain bacteria, within whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Our results suggested that 0.2% C. butyricum decreased the relative abundance of Escherichia_coli and cortisol, endotoxin concentrations in serum of piglets. It is worth mention that piglets can obtain probiotics indirectly from the sow and by her environment, enriched by sow feces or feed spillage (Yan et al, 2019). Several studies have shown that the addition of probiotics in the late pregnancy and lactation period of the sow can reduce the diarrhea and mortality of piglets and improve the growth performance of suckling piglets by inhibiting the proliferation of pathogenic bacteria or by enhancing certain immune mechanisms (Kritas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that 0.2% C. butyricum decreased the relative abundance of Escherichia_coli and cortisol, endotoxin concentrations in serum of piglets. It is worth mention that piglets can obtain probiotics indirectly from the sow and by her environment, enriched by sow feces or feed spillage (Yan et al, 2019). Several studies have shown that the addition of probiotics in the late pregnancy and lactation period of the sow can reduce the diarrhea and mortality of piglets and improve the growth performance of suckling piglets by inhibiting the proliferation of pathogenic bacteria or by enhancing certain immune mechanisms (Kritas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA was extracted from jejunal samples using a DNAiso Reagent (Takara Bio Inc., Dalian, China). The quality control of DNA was performed as previously described [27]. The content of mtDNA relative to nuclear genomic DNA was measured by co-amplifying the mitochondrial DNA-loop ( mt D-loop ) and the nuclear-encoded bet β-actin ( ACTB ) using real-time PCR assay.…”
Section: Methodsmentioning
confidence: 99%
“…Microorganisms DNA were extracted from the intestinal content with the Stool DNA Kit (Omega Bio‐Tek) (Yan, Zhang, Guo, Zhang, & Liu, ). Group‐specific primers of Escherichia coli , Bifidobacterium , Lactobacillus , and Bacteroidetes based on 16S rDNA sequences PCR assay were synthesized commercially by Life Technologies Limited (Table S3).…”
Section: Methodsmentioning
confidence: 99%